Multidisciplinary approach to patients with closed lab and palate and the quality of life (Research, Society and Development, 2023)
Introduction: Cleft lip and palate is an important health adversity, as it affects the patient psychologically, aesthetically and functionally. This deformity affects speech, hearing and appearance, which impairs the individual's social integration, thus interfering with their quality of life. Objective: to demonstrate the importance of a multidisciplinary follow-up to patients with cleft lip and palate. Methodology: The searches for scientific evidence were carried out in databases such as: Virtual Health Library, Scientific Electronic Library Online and PubMed using the search terms: cleft lip, cleft palate and oral health. And so, selected complete and published articles, found in the cited sites. Results: Initially, 231 articles were found. After selection, 9 were suitable for the purposes of the study, the information was transferred to the collection instrument. The included articles were presented in a summary table and the analysis of the results was carried out in a descriptive way, presenting the synthesis of the studies through comparisons and highlighting the differences and/or similarities. Conclusion: consulted, it is concluded that the treatment considered most effective for cleft patients is carried out by a multidisciplinary team composed of several professionals from different areas of health, and that the dentist has a fundamental role in the control of oral infections and aesthetic reestablishment. and functional performance of these patients, thus improving their quality of life.